Does Activator Therapy Change Sagittal Mandibular Dimension and Glenoid Fossa Position? A Clinical Magnetic Resonance Imaging Study - Hatice Gökalp (Galenos Yayinevi, 2007)
The aim of this study was to research whether an activator treatment changes effective mandibular length and glenoid fossa growth direction or not. While treatment group was consisted of nine skeletal Class II patients (7 girls, 2 boys) who having mean age of 11.31 years and were treated with an activator; control group was also consisted of nine patients (7 girls, 2 boys) of 9.97 years with the same malocclusion in early growth period and this cases were untreated orthodontically. Activator was worn 17 hours per-a-day on average 1 year. Mandibular sagittal dimensions (Co-Gn) were evaluated on lateral cephalograms and glenoid fossa position was evaluated by using Magnetic Resonance Imaging (MRI). An increase of 4.73 mm was found in sagittal mandibular dimension in activator group at the end of the Activator. Additionally, it was found that posterior growth direction of the glenoid fossa was changed toward anterior direction. The results of this study revealed that mandibular position and effective mandibular length is changed by activator treatment. Those changes may be a result of changes in the growth directions of glenoid fossa. Thus, it may be concluded that, activators corrects Class ll malocclusion by changing glenoid fossa growth direction.